2006
DOI: 10.1111/j.1744-697x.2006.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenylalanine fermentation byproduct and sugarcane molasses on fermentation quality and rumen degradation of whole crop barley (Hordeum vulgare L.) silage in situ

Abstract: Phenylalanine fermentation byproduct (PFB) is generated by purifying phenylalanine products from microbial fermentation in the food industry. We examined the function of PFB as an ensiling agent to improve the silage fermentation and nutritive value of forage crops. We investigated the fermentation quality and rumen degradability of whole crop barley (Hordeum vulgare L.) silage in situ. We ensiled this type of silage in a laboratory scale using five compositional ratios (v/v) of PFB (20%, 40%, 50%, 60% and 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…a more homolactic fermentation that prevailed during the silage fermentation (Kung et al 2003). Previous studies have reported that the molasses additive decreases the concentrations of AA and PA of silage due to the fact that rapid decline of pH can inhibit undesirable microorganisms' growth (Yunus et al 2000;Wuisman et al 2006;Guo et al 2014). Our results confirmed their findings.…”
Section: Fermentation Characteristics Of Mixed Silagesupporting
confidence: 90%
“…a more homolactic fermentation that prevailed during the silage fermentation (Kung et al 2003). Previous studies have reported that the molasses additive decreases the concentrations of AA and PA of silage due to the fact that rapid decline of pH can inhibit undesirable microorganisms' growth (Yunus et al 2000;Wuisman et al 2006;Guo et al 2014). Our results confirmed their findings.…”
Section: Fermentation Characteristics Of Mixed Silagesupporting
confidence: 90%
“…Dann et al () reported that glutamate supplementation did not affect OM, DM, acid detergent fiber, NDF and non‐structural carbohydrate digestion in a continuous culture study, but CP digestion decreased linearly with increased glutamate supplementation. Wuisman et al () reported that rumen degradability of DM and NDF of the whole plant in situ was also significantly increased by phenylalanine fermentation by‐product. In this study, the increasing NDF digestibility by MSGB treatment with lower ruminal ammonia concentration can explain that MSGB supplementation may synchronize the ammonia and energy availability and improve microbial growth and cellulolytic activity in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…There were many researches which adding additives to enhance the acidification of ensiled forages ( Alli et al, 1984 ; Wuisman et al, 2006 ). Molasses has been used extensively as a fermentation stimulant, since it could provide fermentable substrates for lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%